Zai Gongchandang he Mao zhuxi lingdao xia, ba Zhongguo jianshe chengwei yige fanrong fuqiangde shehui zhuyi guojia! - Ding Hao,
'Turn China into a prosperous, rich and powerful country under the leadership of the Communist Party and Chairman Mao!' Printno. 185. No. BG E13/866 is the same poster.